Can Neuromuscular Electrical Stimulation Enhance the Effect of Sprint Interval Training? - Takeda, Ryosuke; Nojima, Hiroya; Nishikawa, Taichi; Okudaira, Masamichi; Hirono, Tetsuya; Watanabe, Kohei (International Journal of Sports Medicine, 2024)
The aim of this study was to determine the effects of subtetanic neuromuscular electrical stimulation combined with voluntary exercise between repeated Wingate tests on sprint exercise performance and blood lactate accumulation during sprint interval training. Fifteen healthy young males volunteered. After 1-min baseline, participants underwent the Wingate test twice. They performed a 4-min intervention between tests: neuromuscular electrical stimulation with free-weight cycling or voluntary cycling alone [43.6 (8.0) watts], which matched oxygen consumption with neuromuscular electrical stimulation with free-weight cycling. The blood lactate concentration was assessed at the end of the baseline, at 3-min intervention, and on recovery at 1, 3, 5, and 10 min after the second Wingate test. Peak and mean blood lactate concentration during recovery were significantly greater with neuromuscular electrical stimulation with free-weight cycling than voluntary cycling alone (P>0.036 and P=0.011, respectively). Peak power, mean power, and rate of decline (fatigue index) were not significantly different between conditions in both Wingate tests (condition/interaction all P>0.300, partial η2<0.1). Subtetanic neuromuscular electrical stimulation combined with voluntary exercise indicated similar exercise performance and fatigue levels during Wingate tests, but enhanced blood lactate accumulation compared to oxygen consumption-matched voluntary cycling during sprint interval training.
Keywords: subtetanic neuromuscular electrical stimulation; lactate; sprint interval training